Optimizing strategy for training of home blood pressure monitoring in hypertension patients (优化家庭血压测量技术培训在高血压患者健康教育中的应用) - YAO Zhiping (姚志萍) (中西医结合护理)
Objective To investigate the effect of optimized strategy for training of home blood pressure monitoring in hypertension patients. Methods Totally 120 hypertension patients were divided into two group according to the admission time: 60 patients recruited from October 2019 to May 2020 were set as control group, another 60 patients recruited from June 2020 to October 2020 were set as observation group. A routine training of home blood pressure monitoring was adopted in the control group, and optimized strategy for training of home blood pressure monitoring was carried out in the observation group. Level of patient’s knowledge about home blood pressure monitoring and patient’s satisfaction were evaluated after intervention. Results Patients in the observation group achieved higher scores of knowledge assessment and satisfaction compared with those in the control group (P＜0. 05). Conclusion The optimized strategy for training is potentially effective to improve knowledge and self-management skills for blood measurement among hypertension patients. (目的 探讨优化家庭血压测量技术培训在高血压患者健康教育中的应用效果。方法 选取2019年10月—2020年12月医院收治的高血压患者120例为研究对象, 按照时间顺序分组, 将2019年10月—2020年5月收治的60例高血压患者设为对照组, 将2020年6月—12月收治的60例高血压患者设为观察组。对照组采用常规教育方法进行家庭血压测量操作培训, 观察组在对照组基础上实施优化家庭血压测量技术培训。比较2组患者家庭血压测量知识得分及患者满意度得分。结果 观察组患者家庭血压测量知识得分和满意度得分均高于对照组, 差异有统计学意义(P＜0. 01)。结论 实施优化家庭血压测量技术培训可以提高患者家庭血压测量相关知识及满意度, 有助于帮助患者形成良好的血压测量行为, 提高患者自我管理能力。)